Sistem Pakar Untuk Mengidentifikasi Jenis Kulit Wajah dengan Metode Certainty Factor - Santi, Indyah Hartami; Andari, Bina (Universitas Nusantara PGRI Kediri, 2019)
The role of facial beauty experts is vital for identifying the kind of facial skin as well as providing the right treatment solution for every kind of facial skin. From this, an expert system is needed to help provide solutions by building an expert system that can identify the type of facial skin by including treatment solutions. The Certainty Factor method makes a selection based on consideration in the calculation process, and this method looks for the highest combination of trust values. At the beginning of the study data collection was carried out on 40 female respondents obtained 100% of respondents did not understand the type of facial skin and 76% said they needed experts, 95% required an expert system application. While the results of the assessment of the application system that had been built by respondents stated that 88% of the system design was excellent and very good 91% of the system was easy to use, and 98% said the operation was by what was needed.